Zenit RA evaluation, a solid-phase chemiluminescence immunoassay for detection of anti-cellular antibodies. (March 2017) - Melguizo Madrid, Enrique; González-Rodríguez, Concepción; Ávila-García, María de Gracia; Arrobas-Velilla, Teresa; Fernández-Riejos, Patricia
Aim: The objective was to compare Zenit RA chemiluminescent immunoassay (CLIA) from Menarini Diagnostics and ELISA from INOVA Diagnostics for the presence of specific anti-Ro/SS-A, anti-La/SS-B, anti-U1snRNP, anti-Sm, anti-Scl-70, anti-Jo-1 antibodies.Results/methodology: We studied 501 samples (178 connective autoimmune disease, 150 other autoimmune or inflammatory disease and 173 other disease or healthy). All samples were analyzed using CLIA and ELISA. The Kappa agreement was excellent for anti-SSA/Ro (0.864), good for anti-SSB/La (0.735), anti-Scl-70 (0.685) and ENA-screening (0.778), moderate for anti-RNP (0.563) and bad for anti-Sm (0.266) and anti-Jo-1 (0.243). Different combination of cut-off improved the specificity and agreement.Conclusion: Zenit RA CLIA for detecting autoantibodies, provides a simple, useful and accurate tool.